METODE PARTIAL LEAST SQUARE (PLS) DAN TERAPANNYA (Studi Kasus: Analisis Kepuasan Pelanggan terhadap Layanan PDAM Unit Camming Kab. Bone) - Irwan Irwan; Khaeryna Adam (Teknosains, 2015)
Water is primer necessity of human. The needs of clean wateralways increasingly through the time. PDAM or district water supplycompany as a local company that have duty to distribute clean water for thepeoples need to increasing the serve quality for the satisfied of customer.Theaim of this research is to know the influence of PDAM Unit Camming forthe satisfied of customer.Method that used to survey the customer satisfied isSERVQUAL method (Service Quality) that have 5 dimension, such as:Tangible, Reliability, Responsiveness, Assurance, and Emphaty.Analysismethod that used is Partial Least Square (PLS). Theresult of thisresearch is how the 5 dimension of SERVQUAL influence the satisfied ofPDAM Unit Camming customer. Wecan see the result in R square that getby smartPLS helped. Theresult showed 0,706. Its mean, the 5 dimension ofSERVQUAL can explain that 70,6% satisfied of PDAM Unit Cammingcustomer. However, there still have serve quality dimension that need torepair, such as responsiveness and tangible. Thistwo things must be repairedto increasing the serve of PDAM Unit Camming and also can increase thesatisfied of customer.